2007
DOI: 10.1295/polymj.pj2007062
|View full text |Cite
|
Sign up to set email alerts
|

Side-Chain Effects on Friction-Transferred Polymer Orientation

Abstract: ABSTRACT:Effects of substituted side-chains of poly(2,5-dialkoxy-1,4-phenylenevinylene) derivatives (PPV) on polymer orientation have been studied using polarized optical spectroscopy and synchrotron-sourced grazing incidence X-ray diffraction (GIXD) analysis. The results of polarized optical spectroscopy indicate that the symmetrically substituted PPV is suitable for homogeneous oriented film preparation by friction-transfer technique. The formed film of poly(2,5-(2-ethylhexyloxy)-1,4-phenylenevinylene) (BEHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The larger domain size is thought to originate from the fibrillar structure of a larger size as a result of more conjugated backbones. Thirdly, the anisotropy of films crucial for device performances could be controlled by the molecular structures of chains [117][118][119].…”
Section: The Effect Of Planarity and Rigidity On Structure Morphologmentioning
confidence: 99%
See 1 more Smart Citation
“…The larger domain size is thought to originate from the fibrillar structure of a larger size as a result of more conjugated backbones. Thirdly, the anisotropy of films crucial for device performances could be controlled by the molecular structures of chains [117][118][119].…”
Section: The Effect Of Planarity and Rigidity On Structure Morphologmentioning
confidence: 99%
“…As a result, the roughness of films for P3AT with shorter side-chains and more intense conjugation was larger indicating a larger crystallinity, which was the origin of the highest mobility in its film. Besides, a larger dichroic ratio of optical absorption or emission indicating the higher anisotropy of carrier transport could be tuned by the length of side-chains [117,119]. Ren et al reported that with shorter side-chains, the dichroic ratio of films prepared by mechanically shearing turned larger [117].…”
Section: Side-chainsmentioning
confidence: 99%
“…Polymer crystallinity was also found to be an important factor for generating a homogeneous oriented film, with PPV crystallinity strongly depending on the kind of side-chain substitution. Symmetric PPV forming homogeneous oriented films were found to be highly crystalline, whilst asymmetric PPV that did not form homogeneous thin films are amorphous [61]. Hao et al [24] reported thin film formation of a water-soluble poly(phenylenevinylene) (PPV) derivative with sulfonate containing side chains (DPS-PPV) on silica substrates by solvent-free friction transfer at 300 • C. Films were formed by "rods" of polymer aligned perpendicular to the drawing direction, contrasting with the behavior of comparable polymers, which tend to align along the drawing direction.…”
Section: Friction Transfermentioning
confidence: 91%
“…The structure of the side-chains was shown not to affect the friction transfer process only the polymer backbone alignment. The symmetric PPV derivatives (DOPPV, BDMOPPV and BEHPPV) were shown to form oriented and homogeneous films, with BEHPPV displaying the best quality film [61]. By contrast, none of the asymmetric PPV derivatives (MOPPV, BDMOPPV and MEHPPV) formed homogeneous films.…”
Section: Friction Transfermentioning
confidence: 97%
See 1 more Smart Citation